Peran Biblioterapi dalam Mendukung Kognisi Lansia - Patriana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The increasing older adult population requires intervention approaches that can maintain and enhance cognitive functioning in an effective, safe, and accessible manner. This study aims to explain: (1) Bibliotherapy, (2) Older Adults, and (3) The Role of Bibliotherapy in Supporting the Cognitive Abilities of Older Adults. This research employs a qualitative approach using a literature review method. The primary data sources consist of books, scholarly articles, and research findings related to bibliotherapy, reading-based counseling, as well as studies on cognition and the aging process in older adults. Secondary data sources include supporting scientific works such as conference proceedings, popular articles, and additional literature concerning mental health and cognitive functioning in older adults. The data collection technique utilized is literature study. The data analysis process follows the Miles and Huberman model, namely: (1) data reduction, (2) data display, and (3) conclusion drawing and verification. Data validity was ensured through triangulation. The findings of this study indicate that bibliotherapy has the potential to serve as an effective complementary strategy for maintaining and improving cognitive function among older adults.